A Theorem on Technical Progress - Kalecki, M. (Review of Economic Studies, 1941)
Journal Article A Theorem on Technical Progress Get access M. Kalecki M. Kalecki Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 3, June 1941, Pages 178–184, https://doi.org/10.2307/2967601 Published: 01 June 1941